Pharmacological profile of dicaffeoylquinic acids and their role in the treatment of respiratory diseases - Hufnagel, Matthias; Rademaekers, André; Weisert, Anika; Häberlein, Hanns; Franken, Sebastian (Frontiers in Pharmacology, 2024)
Dicaffeoylquinic acids (DCQAs) are polyphenolic compounds found in various medicinal plants such as Echinacea species and Hedera helix, whose multi-constituent extracts are used worldwide to treat respiratory diseases. Besides triterpenes, saponins, alkamides, and other constituents, DCQAs are an important group of substances for the pharmacological activity of plant-derived extracts. Therefore, the pharmacological properties of DCQAs have been studied over the last decades, suggesting antioxidative, anti-inflammatory, antimicrobial, hypoglycaemic, cardiovascular protective, neuroprotective, and hepatoprotective effects. However, the beneficial pharmacological profile of DCQAs has not yet been linked to their use in treating respiratory diseases such as acute or even chronic bronchitis. The aim of this review was to assess the potential of DCQAs for respiratory indications based on published in vitro and in vivo pharmacological and pre-clinical data, with particular focus on antioxidative, anti-inflammatory, and respiratory-related effects such as antitussive or antispasmodic properties. A respective literature search revealed a large number of publications on the six DCQA isoforms. Based on this search, a focus was placed on 1,3-, 3,4-, 3,5-, and 4,5-DCQA, as the publications focused mainly on these isomers. Based on the available pre-clinical data, DCQAs trigger cellular mechanisms that are important in the treatment of respiratory diseases such as decreasing NF-κB activation, reducing oxidative stress, or activating the Nrf2 pathway. Taken together, these data suggest an essential role for DCQAs within herbal medicines used for the treatment of respiratory diseases and highlights the need for the identifications of DCQAs as lead substances within such extracts.